Anticipate : Knowing What Customers Need Before They Do - Thomas, Bill; Tobe, Jeff (Wiley, 2012)
Design and implement the ideal customer focus Anticipate provides business readers with a practical how-to approach for taking their customer-supplier relationship to one that is more sustainable and more mutually profitable. Much of the discussion on customer experience has centered on the hospitality or retail industries and has showcased the discrete techniques organizations use to deliver better service and create more satisfied customers. Anticipate extends and integrates those techniques to deliver an end-to-end customer experience that can be applied in any industry, by any type of organization. Get proven guidance on how to design and implement a customer-focused journey that moves beyond the transaction and satisfied customers, to a relationship and culture that creates and leverages loyalty - and the profitability that comes with it. Explains proprietary methods-such as the Customer Focus Maturity Model and Value Chain Labs -that teach readers the steps and tools organizations use to create, drive and optimize their customer focus. Authors Bill Thomas and Jeff Tobe have used their 10-point framework to guide Fortune 500's, start-ups as well as non-profits in charting a customer-focused journey that matures, anticipates and delivers increasing levels of loyalty and profitability with their customers, and across their broader value chain. Anticipate will provide you with field-proven steps, tools and examples that you'll use to take your customer-focused strategy, execution and culture to the ideal level.